Buddhism and the Scientific Image: Reply to Critics: with Christian Coseru, “Buddhism, Comparative Neurophilosophy, and Human Flourishing”; Charles Goodman, “Buddhism, Naturalism, and the Pursuit of Happiness”; Bronwyn Finnigan, “Examining the Bodhisattva's Brain”; and Owen Flanagan, “Buddhism and the Scientific Image: Reply to Critics.” - Flanagan, Owen (Zygon, 2014)
I provide a précis of The Bodhisattva's Brain: Buddhism Naturalized (), and then respond to three critics, Christian Coseru, Charles Goodman, and Bronwyn Finnigan.